El significado ambivalente del reconocimiento del derecho a la especial protección en Colombia (2017)
This article examines critically the meaning of the legal category of the right to special protection in the Colombian legal system and its relation with the theories of recognition. Firstly, the article argues that this category has a positive and negative meaning which needs to be understood as a political tool in permanent construction, and to be interpreted it in its various dimensions and subdivision. Secondly, the article argues that this right is based on the theories of recognition and, therefore, integrates and articulates to the tensions and problems of the forms of recognition. Thirdly, we present the opposite sides that are normally involved in this kind of legal recognition. From there, the article nurtures the idea, according to which, the right to special protection in Colombia promotes a model of formal and material recognition, not of disadvantaged subjects and groups, that represents their inequality by means of a new discourse of rights under which the old discourse of modern law hides, which, ultimately, ends up questioning the positive meaning of this category and reinforces its negative sense.